Colornames for denotation of the geographical and topographical names in monuments middling Ukrainian and newly Ukrainian language (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2017)
Linguists study the history of color names, their etymology, the process of forming separate groups and their composition at different stages of language development, determine the correlation of each name of the color with the subject-standard. Usually, the analysis of the function of the coloroleks is given in the synchronous aspect. However, the diachronic study of color names is important for the process of formation and functioning of the relevant thematic group, the identification of the regularities of the formation of the historical lexicology of the Ukrainian language in general.A characteristic feature of the monuments of the Middle Ukrainian period is the wide use of color names in the geographical names. Derivatives with a nominal white and its derivatives in geographical names can be combined into separate thematic groups: the names of cities and towns, villages, seas, rivers, tracts. Often, monuments are composed of names of cities with the use of the colored image. There are also separate titles of states. Among the areas of use of black nominae in the Middle Ukrainian language are often used geographical, toponymic names, which are grouped into separate thematic groups (names of cities, countries, toponymic names, names of villages, names of rivers, lakes, seas). A number of new titles show the performance of the color rendering black. For the transfer of red color in the analyzed thematic group used names with ancient roots. The analyzed material confirms the widespread use of collo-Aleksiki in geographical and topographical names during the period under review. Some of the names have occurred in the previous period. The most productive in the worked out thematic group were white, black colors. A wide range of lexemes with different roots for the red color has been revealed. Less productive in the analyzed thematic group were blue, yellow, gray, green.
Keywords: colornames; derivate; thematic group; nomen; derivatives; geographical; topographical names